Modeling the relationship between depression in people with cancer and perceived stress, with the mediating role of eating problems, sexual satisfaction, emotion regulation and self-compassion - Moniri, Reihaneh; Gharraee, Banafsheh; Zahedi Tajrishi, Komeil (Frontiers in Psychology, 2024)
Aim: With the rising prevalence of cancer and the adverse physical and psychological experiences endured by affected individuals, this study aims to establish a model illustrating the relationship between depression in people with cancer and perceived stress. Additionally, it examines the mediating influence of eating problems, sexual satisfaction, emotional regulation, and selfcompassion.Method: This study employs a descriptive-correlational research method, utilizing structural equation analysis (modeling) to explore the role of mediators. The research sample comprised 200 individuals diagnosed with cancer, selected based on predetermined inclusion and exclusion criteria. Participants completed Beck's 13-item depression questionnaire, a 10-item perceived stress questionnaire, an 8-item appetite measurement questionnaire, a 25-item sexual satisfaction questionnaire, a 10-item emotion regulation questionnaire, and a 12-item compassion questionnaire. The data were subsequently analyzed using SPSS-24 and Lisrel 80/8 software.The research findings indicate a significant positive relationship between perceived stress and depression in people with cancer. Furthermore, eating problems exhibited a mediating role in the relationship between perceived stress and depression, with a direct effect coefficient of (t=0.28, ß=0.02). However, the path from perceived stress to depression, mediated by sexual satisfaction, was found to be statistically insignificant, with a standard coefficient of 0.01 at the p<0.05 level. Emotion regulation demonstrated a direct effect coefficient of (t=-3.52, ß=-0.33) on depression. Likewise, self-compassion exhibited a direct effect coefficient of (t=-3.08, ß=-0.28) on depression, while the path from perceived stress to depression was mediated by selfcompassion, with a standard coefficient of 0.12 at the p<0.05 level.In conclusion, this study sheds light on the interplay between depression and perceived stress in individuals with cancer, revealing a significant positive association. Eating